Convenient Synthesis of 2-(2,2-Difluoroethoxy)-6-(trifluoromethyl)-benzenesulfonyl Chloride, A Key Building Block of Penoxsulam - Huang, Shuai Shuai; Zheng, Zhan Jiang; Cui, Yu Ming; Xu, Zheng; Yang, Ke Fang; Xu, Li Wen (Synthesis, 2019)
A convenient and efficient three-step synthesis of 2-(2,2-difluoroethoxy)-6-(trifluoromethyl)benzenesulfonyl chloride, the key building block of penoxsulam, is described. The main features of the synthesis include a regioselective lithiation and subsequent electrophilic substitution starting from commercially available 3-bromobenzotrifluoride to provide (2-bromo-6-(trifluoromethyl)phenyl)(propyl)sulfane, then a copper-catalyzed C–O coupling to introduce the difluoroethoxy moiety and chloroxidation conditions to give the desired sulfonyl chloride.
Keywords: penoxsulam; regioselective lithiation; benzyne intermediate; C–O coupling; chloroxidation